The State in Early Modern Russia : New Directions - Bushkovitch, Paul (Book collections on Project MUSE., 2019)
"The State in Early Modern Russia: New Directions is an attempt to understand the character and development of the Russian state in the early modern era (1500-1800)in new ways. Going beyond traditional scheme of autocracy, the articles show the state as a complex institution with different relations to society and with an important role in religion and culture."--Provided by publisher.